Autonomic Nervous System Function Following Prenatal Opiate Exposure - Hambleton, Matthew T.; Reynolds, Eric W.; Sithisarn, Thitinart; Traxel, Stuart J.; Patwardhan, Abhijit; Crawford, Timothy N.; Mendiondo, Marta; Bada, Henrietta S. (Frontiers in Pediatrics, 2013)
In utero exposure to opiates may affect autonomic functioning of the fetus and newborn. We investigated heart rate variability (HRV) as a measure of autonomic stability in prenatal opiate exposed neonates (n=14) and in control term infants (n=10). Electrocardiographic data during both non-nutritive and nutritive sucking were evaluated for RR intervals, heart rate (HR), standard deviation of the RR intervals (SDRR), standard deviation of the differences of subsequent RR intervals (SDDRR), and the power spectral densities in low and high frequency bands. In controls, mean HR increased significantly, 143/min to 161/min (p=0.002), with a trend toward a decrease in RR intervals from non-nutritive to nutritive sucking; these measures did not change significantly among exposed infants. Compared to controls, exposed infants demonstrated significantly greater HRV or greater mean SDRR and SDDRR during non-nutritive period (p<0.01), greater mean SDDRR during nutritive sucking (p=0.02), and higher powers in the low and high frequency bands during nutritive feedings. Our findings suggest that prenatal opiate exposure may be associated with changes in autonomic nervous system functioning involving both sympathetic and parasympathetic branches. Future studies are needed to examine the effects of prenatal opiate exposure on ANS function.